Up-regulated expression of two-pore domain K+ channels, KCNK1 and KCNK2, is involved in the proliferation and migration of pulmonary arterial smooth muscle cells in pulmonary arterial hypertension - Shima, Natsumi; Yamamura, Aya; Fujiwara, Moe; Amano, Taiki; Matsumoto, Kazuyuki; Sekine, Taiga; Okano, Haruka; Kondo, Rubii; Suzuki, Yoshiaki; Yamamura, Hisao (Frontiers in Cardiovascular Medicine, 2024)
Pulmonary arterial hypertension (PAH) is a severe and rare disease in the cardiopulmonary system. Its pathogenesis involves vascular remodeling of the pulmonary artery, which results in progressive increases in pulmonary arterial pressure. Chronically increased pulmonary arterial pressure causes right ventricular hypertrophy and subsequent right heart failure. Pulmonary vascular remodeling is attributed to the excessive proliferation and migration of pulmonary arterial smooth muscle cells (PASMCs), which are induced by enhanced Ca 2+ signaling following the up-/down-regulation of ion channel expression. In the present study, the functional expression of two-pore domain potassium KCNK channels was investigated in PASMCs from idiopathic PAH (IPAH) patients and experimental pulmonary hypertensive (PH) animals. In IPAH-PASMCs, the expression of KCNK1/TWIK1 and KCNK2/TREK1 channels was up-regulated, whereas that of KCNK3/TASK1 and KCNK6/TWIK2 channels was down-regulated. The similar up-regulated expression of KCNK1 and KCNK2 channels was observed in the pulmonary arterial smooth muscles of monocrotaline-induced PH rats, Sugen 5416/hypoxia-induced PH rats, and hypoxia-induced PH mice. The facilitated proliferation of IPAH-PASMCs was suppressed by the KCNK channel blockers, quinine and tetrapentylammonium. The migration of IPAH-PASMCs was also suppressed by these channel blockers. Furthermore, increases in the proliferation and migration were inhibited by the siRNA knockdown of KCNK1 or KCNK2 channels. The siRNA knockdown also caused membrane depolarization and subsequent decrease in cytosolic [Ca 2+ ]. The phosphorylated level of c-Jun N-terminal kinase (JNK) was elevated in IPAH-PASMCs compared to normal-PASMCs. The increased phosphorylation was significantly reduced by the siRNA knockdown of KCNK1 or KCNK2 channels. Collectively, these findings indicate that the up-regulated expression of KCNK1 and KCNK2 channels facilitates the proliferation and migration of PASMCs via enhanced Ca 2+ signaling and JNK signaling pathway, which is associated with vascular remodeling in PAH.